Evaluation of the thermal performance of a box type solar cooker in the rainy season in a sub-Saharan country - Soro, D.; Doumbia, Y.; Marí, B.; Fofana, B.; A. YAO, N.; Touré, S.; Aka, B. (International Journal of Engineering and Technology, 2020)
This article deals with the calculation of the performance parameters of a box-type solar cooker in a sub-Saharan country in the rainy season where the solar activity is considerably attenuated because of the numerous cloudy periods. The various tests were carried out at the Labora-tory of Fundamental and Applied Physical Sciences of the École Normale Supérieure (ENS) in Abidjan. During these cooking tests, the illuminance was measured. The temperatures of the ambient air and of various places of the solar cooker were also recorded. Illumination measurements made with an EPPLEY type pyranometer made it possible to determine the average illuminance which oscillates between 636.98 w / m² and 517.91w / m² depending on the day. The average energy efficiency of the cooker has been calculated for the cooking of several foods. It varies between 20.48 ٪ to 26.59%. The overall loss coefficient is between 5.63 and 5.82. The results obtained for these tests are satisfactory and very encouraging, especially since they were carried out in the rainy season.